Post COVID-19 Era and the Role of Accountants in the Recovery of Nigeria’s Economy - NWAFOR, Samuel Ikechukwu (Socialscientia: Journal of Social Sciences and Humanities, 2021)
This work is on the role of Accountants in the recovery of Nigeria’s economy and the challenge(s) militating against successful execution of the tasks in the post COVID-19 era. Secondary sources of related literatures were carefully reviewed with emphasis on the role of accountants in economic development and growth, in the post COVID-19 era, and in economic recovery in the COVID-19. The study revealed that Accountants play effective roles in engineering positive change towards recovering Nigeria economy in the post COVID-19 era. The findings of the study indicate that as the managers of financial resources, Accountants are in the best position to advise policy makers on the best way to go in managing the National economy. The study also revealed that economic recovery may pose a little difficulty in the midst of misappropriation and embezzlement, as corruption is identified as a major factor militating against quick recovery of Nigeria economy in the post COVID-19 era. Notwithstanding, Accountants are trained to be at the front seat in the fight against fraud. This however will not be an easy task as the mix of accounting, law, and IT skills are required for accountants to be well positioned to effectively fight fraud. To effectively play the aforementioned roles towards recovering Nigeria Economy in the post COVID-19 era, professional bodies and other relevant authorities should hasten up to make accounting curriculum more elaborate and enriching with modern accounting principles, concepts and conventions in the face of present day economic challenges. Accountants should facilitate the establishment and implementation of functional internal control system in every organization they find themselves.